Surgical Management of Intracranial Meningiomas in the Elderly: Early and Long-term Outcomes - Czernicki T (Dove Medical Press, 2020)
Tomasz Czernicki Department of Neurosurgery, Medical University of Warsaw, Warsaw, PolandCorrespondence: Tomasz CzernickiDepartment of Neurosurgery, Medical University of Warsaw, Banacha Street 1A, Warsaw 02-097, PolandTel +48225992575Fax +48225991574Email tczernicki@wp.plPurpose: In view of the risk associated with the surgical treatment of intracranial meningiomas in the elderly population due to the physiology of aging and multiple comorbidities, an attempt was made to identify factors influencing outcomes and to define the subgroup of patients who should not be operated on due to poor results.Patients and Methods: A retrospective analysis of 58 patients over 70 years old with assessment of short-term and long-term outcomes. Scores by previously described CRGS, SKALE, and GSS grading systems were also calculated for our patients.Results: Neurological morbidity was only associated with a critical location according to the SKALE grading system (P=0.02). Six patients (10.3%) died. Mortality was associated with the Karnofsky Performance Scale score (KPS ≤ 60 vs KPS ≥ 70; P=0.0162), the American Society of Anesthesiologists scale status (ASA 1 or 2 vs ASA 3; P=0.0022) and the WHO grade of meningiomas (P=0.012). Risk factors for tumor recurrence (six patients) were WHO grade (P=0.00048) and Simpson grade of resection (P=0.0437). At follow-up, excluding patients who died due to surgery or recurrence (15.5%), most patients improved (50%) or remained unchanged (25.9%) in relation to the preoperative KPS status.Conclusion: Postoperative neurological deterioration was only associated with a critical tumor location (skull base, eloquent area, large vessels involvement by the tumor). Due to a significantly higher risk of death, careful consideration should be taken for surgery in patients in a poor functional condition (KPS ≤ 60) or in a poor physical condition (ASA 3 status). An improvement or at least nonworsening of the neurological status in relation to the preoperative condition was observed in the majority of patients during follow-up.Keywords: intracranial meningioma, elderly, brain surgery, prognostic factors, complications, recurrence, survival